Digital game-based value learning model for management students in Malaysian higher education institutions / Marha Abdol Ghapar ... [et al.] - Abdol Ghapar, Marha; Ibrahim, Norlaila; Shamsudin, Azlina; Nik Hassan, Nik Fakrulhazri (Universiti Teknologi MARA, Kedah, 2024)
This concept paper proposes integrating explicit, implicit, and social education values into the Game-Based Learning Model to enhance Malaysian higher education. As the world embraces the 4th Industrial Revolution (IR4.0), higher education must adapt digitally to prepare students for post-graduation realities. The primary objective is to explore education values within learning circles of the Game-Based Learning Model. The secondary objective is to merge these values into the existing model, leading to validation within the new Digital Game-Based Value Learning Framework. Qualitative methods, including semi-structured interviews with 10 to 12 purposively sampled management students experienced in digital game-based learning, will be employed for data collection. Findings aim to augment the current model in line with the Ministry of Higher Education's digitalisation agenda. Researchers anticipate the Climb the Corporate Ladder (CTCL) Virtual Board Game to offer significant educational value, aiding in achieving research objectives.